INSTITUTIONAL CHANGES AND POLITICAL STABILITY IN THE KYRGYZ REPUBLIC - A. O. Blokhina (Vestnik MGIMO-Universiteta)
The article analyzes the impact of 2016 amendments to the Constitution of the Kyrgyz Republic on maintaining and strengthening of political stability in the country, which was the official goal of the amendments. The author focuses on new elements in the sphere of division of powers between the head of state, the prime minister, and the legislative power. There are two aspects to the analysis: the normative and the empirical. The main analytical tool was the model of relationship between presidents and assemblies, devised by M. S. Shugart and J. M. Carey.The articlealso utilizes the neo-institutional approach, which can account for the influence of informal political norms and practices when evaluating various institutional patterns. In particular, it examines such peculiarities of the Kyrgyz society as ethnocultural dividedness and neopatrimonial political and cultural orientations. The author concludes that alterations made to the institutional framework of relationship between the president, the head of parliament, and the parliament, and to the growth of responsibility and discipline of deputies may have a positive effect on maintaining of political stability especially given the level of institutionalization of the party system rises.